Ventricular fibrillation in a left ventricular assist device patient: Can the echocardiogram be misleading?. (28th January 2021) - Singh, Manavotam; Malik, Nitin; Brar, Vijaywant; Bering, Patrick T.; Hadadi, Cyrus; Sheikh, Farooq H.; Lam, Phillip H.
Abstract: Sustained ventricular tachycardia and ventricular fibrillation (VF) are life‐threatening arrhythmias which remain highly prevalent in patients with advanced heart failure. These ventricular arrhythmias may impair the support provided by continuous‐flow left ventricular assist devices (CF‐LVADs) and lead to frequent hospitalizations, antiarrhythmic medication use, external defibrillations, and need for heart transplantation. We report a case in which a patient with a CF‐LVAD and an implantable cardioverter defibrillator at end of life presented with asymptomatic low‐flow alarms and was found to have VF of unknown duration. Unique in our case was the presence of apparent organized contractility and rhythmic opening of the mitral valve on echocardiogram despite VF on electrocardiogram.